2022
DOI: 10.1186/s12886-021-02228-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity density alterations in children with strabismus and amblyopia based on resting-state functional magnetic resonance imaging (fMRI)

Abstract: Purpose To explore functional connectivity density (FCD) values of brain areas in children with strabismus and amblyopia (SA) based on blood oxygen level-dependent (BOLD) signals. Methods This study recruited 26 children (14 male, 12 females) with SA and 26 healthy children (14 male, 12 female) as healthy controls (HCs). Both groups matched in age, gender, educational level and socioeconomic background. While resting, all participants underwent fMR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In the correlation analysis between the ROIs and behavioral performance (accuracy) in a key-press decision task, it was observed that in the NG group, activation in the left rectus gyrus, bilateral thalamus, and left temporal pole showed a significant negative correlation with accuracy during the key-press decision phase. The rectus gyrus is associated with episodic memory ( Feng et al, 2020 ), the thalamus is involved in visual information processing ( Shi et al, 2022 ), and the temporal pole plays an important role in perceptual processing ( Bangert and Altenmuller, 2003 ). This finding suggests that the activation in these brain regions in the novice group may be associated with lower decision-making ability or uncertainty, leading to decreased accuracy in decision-making behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In the correlation analysis between the ROIs and behavioral performance (accuracy) in a key-press decision task, it was observed that in the NG group, activation in the left rectus gyrus, bilateral thalamus, and left temporal pole showed a significant negative correlation with accuracy during the key-press decision phase. The rectus gyrus is associated with episodic memory ( Feng et al, 2020 ), the thalamus is involved in visual information processing ( Shi et al, 2022 ), and the temporal pole plays an important role in perceptual processing ( Bangert and Altenmuller, 2003 ). This finding suggests that the activation in these brain regions in the novice group may be associated with lower decision-making ability or uncertainty, leading to decreased accuracy in decision-making behavior.…”
Section: Discussionmentioning
confidence: 99%
“…According to the pathogenesis of amblyopia, which is eyesight weakness due to qi deficiency, our research group has developed an acupuncture method to regulate qi and clear the eyes by selecting Jingming (BL1), Cuanzhu (BL2), Guangming (GB37), and Fengchi (GB20) acupoints, and conducted experimental studies based on the macroscopic perspective of synaptic structure [12][13][14] , which have shown good clinical effects [15] . Because the lesions of amblyopia are in the visual cortex rather than in the retina and resting state-functional magnetic resonance imaging (rs-fMRI) can noninvasively study the brain activity, rs-fMRI technology is widely used to study the brain function changes of amblyopia patients [16][17][18] . Voxelmirror homotopic connectivity (VMHC) is a method proposed by Stark et al [19] in 2008 to study the difference in functional connectivity among the voxels in the symmetrical system of the bilateral hemispheres of the brain and to evaluate its coordination.…”
Section: Introductionmentioning
confidence: 99%